A study on syntactic and pragmatic features of insertion sequence in english and vietnamese (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Insertion sequences are an interesting and common phenomenon of language. They are used a lot in daily human communication. This research offers an analysis of insertion sequence in English and Vietnamese. The aims of the study are to examine insertion sequence in terms of syntax and pragmatics in English and Vietnamese and find out the similarities and differences between them. In addition, the study suggests some implications for the teaching and learning of English as a foreign language in Vietnam. The study is executed in a contrastive analysis of insertion sequence in English and Vietnamese. In order to obtain these aims, a quantitative method, a qualitative method and a descriptive method are taken into account. The study focuses on the investigation of the syntactic and pragmatic features of English and Vietnamese insertion sequence based on the research data collected from English and Vietnamese sources such as books, stories, films and the Internet.